Essential phospholipids prevent islet damage induced by proinflammatory cytokines and hypoxic conditions. Issue 3 (28th October 2015) - Shahbazov, Rauf; Kanak, Mazhar A.; Takita, Morihito; Kunnathodi, Faisal; Khan, Omar; Borenstein, Nofit; Lawrence, Michael C.; Levy, Marlon F.; Naziruddin, Bashoo
Abstract: Background: The pancreatic islet damage that occurs through an inflammatory response and hypoxia after infusion is a major hurdle in islet transplantation. Because essential phospholipids (EPL) have been shown to exhibit anti‐inflammatory properties in liver disease, we analysed their protective effect on islets in inflammatory or hypoxic conditions. Methods: We evaluated the viability of mouse and human islets cultured with cytokines or in hypoxic conditions for 48 h and measured cytokine expression in islets by quantitative polymerase chain reaction. We then employed an in vivo mouse assay, transplanting a marginal dose of human islets treated with or without EPL into the subcapsule of the kidney in diabetic nude mice and determining the cure rate. Results: The viability of mouse and human islets damaged by cytokines was significantly improved by supplementation of EPL in the culture ( p = 0.003 and <0.001 for mouse and human islets respectively). EPL significantly inhibited intracellular expression of IL‐1β and IL‐6 in cytokine‐damaged human islets ( p < 0.001). The viability of human islets in hypoxic conditions was significantly better when treated with EPL ( p < 0.001). In the in vivo mouse assay, the EPL‐treated islet group had a higher cure rate than the untreated control, with marginal statistical significance (75 and 17% respectively, p = 0.07). Conclusions: EPL could be a potent agent to protect islets from inflammatory and hypoxic conditions after isolation procedures. Further studies to clarify the effect of EPL in islet transplantation are warranted. Copyright © 2015 John Wiley & Sons, Ltd.